A green method to extract rutin from Sophora japonica L. - Nhan Trong Le; Trieu Phat Dac Nguyen; Duc Viet Ho; Huong Thanh Phung; Hoai Thi Nguyen (MethodsX, 2023)
Sophora japonica L. contains high levels of rutin, which has great potential for use in pharmaceutical products for the treatment of diseases related to the cardiovascular and circulatory systems. We proposed a method of extracting rutin from S. japonica by using a green solvent. • Green deep eutectic solvents (DESs) of choline chloride and ethylene glycol (ChCl-Eth) showed the highest extraction efficiency of rutin from S. japonica. • Under optimal conditions, the extraction yield of ChCl-Eth was 1.34 times higher than that of methanol as solvent. • Rutin was recovered from the DES extracts using water as the antisolvent with a high recovery yield, and the DESs of ChCl-Eth could be productively recovered and reused at least 3 times.